Conceptualization of Basic Principles and Values in Islamic Education Policy: Principles and Ethics from an Islamic Perspective - Fenny Erdiyani (Responsive: Jurnal Manajemen Pendidikan Islam, 2026)
Islamic education plays a strategic role in shaping a generation of faithful, noble characters, and contributing to national development. However, Islamic education policy in Indonesia often faces problems, such as biases from pragmatic, political, and technocratic interests that cause the normative principles and basic values of Islamic teachings to be neglected. This study aims to formulate a conceptual framework regarding the principles, basic values, principles, and ethics in Islamic education policy. The method used is library research by analyzing primary sources (the Qur'an, hadith, Law No. 20 of 2003) as well as secondary literature in the form of books and scientific articles. The results show that the principles of Islamic education include monotheism, justice, freedom, equality, and deliberation, while its basic values include divine, human, moral, social, and scientific. The principles of Islamic education policy are based on justice, benefit, accountability, and trustworthiness, while its ethics emphasize monotheism, social justice, honesty, and responsibility. This finding emphasizes the importance of making Islamic principles and basic values not merely normative guidelines, but also a practical basis for developing educational policies that are fair, sustainable, and in line with the main goal of Islamic education, namely to form perfect human beings.